Balance in Blind Subjects: Cane and Fingertip Touch Induce Similar Extent and Promptness of Stance Stabilization - Sozzi, Stefania; Decortes, Francesco; Schmid, Monica; Crisafulli, Oscar; Schieppati, Marco (Frontiers in Neuroscience, 2018)
Subjects with low vision often use a cane when standing and walking in everyday life. One aim of this study was to assess differences in body stabilizing effect produced by contact of the cane with the ground or by fingertip touch of a firm surface. Another aim was to estimate the promptness of balance stabilization (or destabilization) on adding (or withdrawing) haptic input from cane or fingertip. Twelve blind subjects and two subjects with severe visual impairment participated in two protocols while maintaining the tandem Romberg posture on a force platform. In one protocol, subjects lowered the cane to a second platform on the ground and lifted it in sequence at their own pace. In the other protocol, they touched an instrumented pad with the index finger and withdrew the finger from the pad in sequence. In both protocols, subjects were asked to exert a force not granting mechanical stabilization. Under steady-state condition, finger touch or contact of the cane with the ground significantly reduced (to ̴78% and ̴86%, respectively) the amplitude of medio-lateral oscillation of the centre of foot pressure. Oscillation then increased when haptic information was removed. The delay to the change in body oscillation after haptic shift was longer for addition than withdrawal of haptic information ( ̴ 1.4s and ̴ 0.7s, respectively; p<0.001), but was not different between the two haptic conditions. Similar stabilizing effects of input from cane and from fingertip touch, and similar latencies to integrate haptic cue from both sources, suggest that the process of integration of the input for balance control is initiated by the haptic stimulus at the interface cane-hand. Use of a tool is as helpful as fingertip input, and does not produce different stabilization. Further, the latencies to haptic cue integration (from fingertip or cane) are similar to those found in a group of sighted subjects, suggesting that integration delays for automatic balance stabilization are unmodified by visual impairment. Haptic input from a tool is easily exploited by the neural circuits subserving automatic balance stabilization in blinds, and its use should be enforced by sensory-enhancing devices and appropriate training.